Implementasi Konsep Fungsi dalam Perancangan Basis Data Sederhana pada Sistem Informasi Akademik - Muhammad Ulya Farhan Farhan; Maryana; Dio Tri Firnanda; Muhammad Rasyya Alfarisi; Muhammad Lukmanul Hakim (JIKUM: Jurnal Ilmu Komputer, 2026)
Good database design is the foundation of a reliable Academic Information System (SIAKAD). However, manydesigners work intuitively without a solid theoretical basis, making them prone to redundancy and operationalanomalies. This study examines the implementation of functions in discrete mathematics as a formal basis for SIAKADrelational database design.The method uses a literature review with a comparative conceptual analysis approach,including identifying SIAKAD entities, mapping function concepts to functional dependencies, analyzing functionaldependencies, normalization up to the third normal form (3NF), and modeling relational schemas.The results show adirect correspondence between mathematical functions and relational database elements: function domains relate toprimary keys, codomains to non-key attributes, injective functions to UNIQUE constraints, surjective functions toFOREIGN KEY coverage, and composite functions to transitive dependencies. Applying this mapping to the SIAKADcase study yielded four normalized relational schemas, Student, Course, Lecturer, and Grade, which are free fromredundancy and data anomalies. This research provides a systematic conceptual framework for database designers tointegrate discrete mathematics principles into the design process.